L'écotoxicologie en questions - Lamy, Isabelle (éditions Quae, 2022)
In a context where we are increasingly able to detect and quantify contaminants and highlight their effects on organisms, what can ecotoxicology contribute today? A better understanding of the problems linked to contaminants, which could lead to overprotective measures? Or a better understanding of the mechanisms and processes involved to better manage the ecotoxicity of substances in the environment? This book addresses the major current approaches in ecotoxicology through open questions that readers who are curious to learn more about this discipline or, more generally, who are concerned about environmental issues, may ask themselves. The answers to these questions provide an overview of the main notions of ecotoxicology and the main associated concepts, and explain the changes that have transformed the traditional approaches to this science into a more holistic approach that takes into account the complexity of real-life conditions. Focusing on ecotoxicological processes and mechanisms enables the causal relationships between the presence and ecotoxicity of contaminants to be addressed, both in terrestrial and aquatic environments. The pursuit of progress in ecotoxicological science is now a major challenge in accounting for the relationship between health and the environment (Eco-Health concept).